Art Education in Türkiye during the Republican Period (1938-1950) - Karaoğlu, Mehmet; Yurtoğlu, Nadir (Institute of Education Sciences, Eskisehir Osmangazi University, 2024)
The subject of the article is the studies carried out on art education in Türkiye during the period from 1938 to 1950 when İsmet İnönü was the President. Under the main title of Art Education in the I. İnönü Period (1938-1950), this article focuses on decisions on art education in National Education Councils (1928-1949), Art Education in Curricula (1938-1950), Art Education in Primary School Curricula, Art Education in Secondary School Curricula, Village Institutes Curricula and Art Education. During the Presidency of İsmet İnönü (1938-1950), the reforms and structures implemented in education, the national education councils conducted by the CHP, and the reports prepared by foreign experts who were invited to Türkiye by the Ministry of National Education for their recommendations on art education formed the basis of this research. In addition, the curriculum programs of primary and secondary schools and Village Institutes are also included in the article's subject. Related documents from the Presidential Archive of the Republic, Official Gazette, minutes and law journals of the Grand National Assembly of Türkiye, various magazines, newspapers, books, and articles from periodical publications were used to collect data. These data were analyzed using the document analysis method.
Keywords: Sosyal Bilgiler Eğitimi; Social Studies Education; History Education; Tarih Eğitimi; İnönü period; art education; national education councils; curriculum; republican people